The Impact of Repeated Reading on the Reading Prosody and Reading Attitudes of Sixth Grade Students with Learning Disabilities - Fox, Brinkley (My University, 2016)
The purpose of this action research study was to investigate the effects of repeated readings on the reading prosody and reading attitudes of sixth grade students with learning disabilities. This single-subject pre-test post-test design study included students within an Exceptional Children’s classroom where they received supplemental reading instruction in addition to regular reading instruction in the general classroom. Each student participated in the repeated reading intervention eight times over a span of seven weeks. Results suggest that the intervention positively impacted prosodic reading, while its impact on reading attitude was undetermined.
Keywords: Reading attitudes; Learning disabilities; Repeated reading invervention; Reading prosody; Elementary school